Milking Sterne’s Subscription Lists, and Extrapolations Therefrom - Walker, Robert G (Library, 2024)
Abstract In the eighteenth century many books were published with lengthy lists of the names, at the front, or occasionally at the back, of those who subscribed to the publication. Scholars have sometimes turned to these lists to make a point about the author or work involved, but it is fair to say that there has never been a consistent attempt to identify and make use of the subscribers of a specific author until just recently, when the publication of an identification list of Laurence Sterne’s subscribers appeared as part of the Florida Edition of Sterne’s works. This article identifies several Sterne subscribers hitherto unidentified or under-identified, discusses techniques for doing so and pitfalls in such techniques, and, finally, makes a case for the usefulness of such identifications both to literary critics and to social historians interested in Sterne’s work.